Toward an inclusive evidence-based practice model: Embracing a broader conception of professional knowledge in health care and health care higher education - Dahl-Michelsen, Tone; Kinsella, Elizabeth Anne; Groven, Karen Synne (Critical Studies in Teaching and Learning, 2023)
Evidence-based practice (EBP) and the evidence-based practice model (EBPM) are currently taken for granted as a guide for teaching and learning ‘best practice’ in higher education health care programs. As health care educators and researchers, we argue for enhancement of the model by inclusion of a broader conception of professional knowledge, including ethical care. In this conceptual paper, we draw on hermeneutic inquiry to reflect on theoretical underpinnings informing earlier discussions of EBP and the EBPM. Also, we enhance our critical thinking by turning to Aristotle. Taken together our reflections bring to the fore an awareness of conflicting logics embedded in the EBPM. We contend that an Aristotelian understanding, however, allows professional knowledge to be reinvigorated by bolstering possibilities for pluralistic conceptions of knowledge. In conclusion, we propose an elaborated EBPM termed the inclusive EBPM. The model includes ethical care as a to guide to teaching and learning of ‘best practice’.